Investigating the Impact of NGSS-Aligned Professional Development on PreK-3 Teachers' Science Content Knowledge and Pedagogy. Issue 7 (23rd November 2016) - Tuttle, Nicole; Kaderavek, Joan N.; Molitor, Scott; Czerniak, Charlene M.; Johnson-Whitt, Eugenia; Bloomquist, Debra; Namatovu, Winnifred; Wilson, Grant
Abstract: This pilot study investigates the impact of a 2-week professional development Summer Institute on PK-3 teachers' knowledge and practices. This Summer Institute is a component of [program], a large-scale early-childhood science project that aims to transform PK-3 science teaching. The mixed-methods study examined concept maps, lesson plans, and classroom observations to measure possible changes in PK-3 teachers' science content knowledge and classroom practice from 11 teachers who attended the 2014 Summer Institute. Analysis of the concept maps demonstrated statistically significant growth in teachers' science content knowledge. Analysis of teachers' lesson plans demonstrated that the teachers could design high quality science inquiry lessons aligned to the Next Generation Science Standards following the professional development. Finally, examination of teachers' pre- and post-Summer Institute videotaped inquiry lessons showed evidence that teachers were incorporating new inquiry practices into their teaching, especially regarding classroom discourse. Our results suggest that an immersive inquiry experience is effective at beginning a shift towards reform-aligned science and engineering instruction but that early elementary educators require additional support for full mastery.